Effect of Pretreatment with Sulfuric Acid on Catalytic Hydrocracking of Fe/AC Catalysts - Ruiyu Wang; Fei Wang; Ling Liu (Journal of Spectroscopy)
Activated carbon (AC) was modified by H2SO4 and used as a support for catalyst. The Fe2S3/AC-T catalyst was prepared by deposition-precipitation method and used to catalyze hydrocracking of coal-related model compound, di(1-naphthyl)methane (DNM). The properties of catalyst were studied by N2 adsorption-desorption, X-ray diffraction, and scanning electron microscopy. The result showed that ferric sulfate and acidic centers had synergetic effect on hydrocracking of DNM when using Fe2S3/AC-T as catalyst, the optimal loading of Fe is 9 wt.%. Hydroconversion of the extraction residue from Guizhou bituminous coal was also studied using Fe2S3/AC-T as the catalyst. The reaction was conducted in cyclohexane under 0.8 Mpa of initial hydrogen pressure at 310°C. The reaction mixture was extracted with petroleum ether and analyzed by GC/MS. Amounts of organic compounds which fall into the categories of homologues of benzene and naphthalene were detected. It suggested that the catalyst could effectively catalyze the cleavage of C-C-bridged bonds.